From ordinary to extraordinary: A framework of experience types. (20th October 2018) - Duerden, Mat D.; Lundberg, Neil R.; Ward, Peter; Taniguchi, Stacy T.; Hill, Brian; Widmer, Mark A.; Zabriskie, Ramon
Abstract: Understanding the nature of, and how to design, structured experiences has become an increasingly salient topic for academics and professionals over the past two decades. Despite the rise in interest in experiences, the related academic literature is fragmented and often atheoretical. To address this situation, this article presents a framework of experiences—including construct definitions and propositions—to help guide the research and design experiences. The framework considers the realm of all possible experiences from subconscious to conscious and subdivides conscious experiences into ordinary and extraordinary dimensions. The framework further classifies extraordinary experiences as memorable, meaningful, and transformational. The distinction between the classes of extraordinary experiences are based on key characteristics of emotion, discovery, and change.